2019
DOI: 10.1029/2018ja026238
|View full text |Cite
|
Sign up to set email alerts
|

Outer Van Allen Radiation Belt Response to Interacting Interplanetary Coronal Mass Ejections

Abstract: We study the response of the outer Van Allen radiation belt during an intense magnetic storm on 15-22 February 2014. Four interplanetary coronal mass ejections (ICMEs) arrived at Earth, of which the three last ones were interacting. Using data from the Van Allen Probes, we report the first detailed investigation of electron fluxes from source (tens of kiloelectron volts) to core (megaelectron volts) energies and possible loss and acceleration mechanisms as a response to substructures (shock, sheath and ejecta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 88 publications
(111 reference statements)
3
26
0
Order By: Relevance
“…We found that for these subsets the majority of events compressed the magnetopause significantly, beyond <8 R E , and typically this occurred at least 50% time of the sheath duration, while clearly a smaller fraction of events led to a compression beyond geostationary orbit, and it occurred typically only for relatively short fraction of sheath duration. We however note that even a relatively short period of compression beyond or close to geostationary orbit can empty quickly in particular the outer parts of the outer Van Allen radiation belts (e.g., Kilpua et al, ). As the fast‐ and strong‐ejecta sheaths have also typically strong magnetic field fluctuations, high dyn pessure, and moderate to intense ring current response, they are expected to cause particularly strong and deep losses of relativistic electrons from the outer radiation belt due to effective magnetopause shadowing (Hietala et al, ; Kilpua, Hietala, et al, ; Kilpua et al, ; Turner et al, ).…”
Section: Summary and Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We found that for these subsets the majority of events compressed the magnetopause significantly, beyond <8 R E , and typically this occurred at least 50% time of the sheath duration, while clearly a smaller fraction of events led to a compression beyond geostationary orbit, and it occurred typically only for relatively short fraction of sheath duration. We however note that even a relatively short period of compression beyond or close to geostationary orbit can empty quickly in particular the outer parts of the outer Van Allen radiation belts (e.g., Kilpua et al, ). As the fast‐ and strong‐ejecta sheaths have also typically strong magnetic field fluctuations, high dyn pessure, and moderate to intense ring current response, they are expected to cause particularly strong and deep losses of relativistic electrons from the outer radiation belt due to effective magnetopause shadowing (Hietala et al, ; Kilpua, Hietala, et al, ; Kilpua et al, ; Turner et al, ).…”
Section: Summary and Discussionmentioning
confidence: 93%
“…We however note that even a relatively short period of compression beyond or close to geostationary orbit can empty quickly in particular the outer parts of the outer Van Allen radiation belts (e.g., Kilpua et al, ). As the fast‐ and strong‐ejecta sheaths have also typically strong magnetic field fluctuations, high dyn pessure, and moderate to intense ring current response, they are expected to cause particularly strong and deep losses of relativistic electrons from the outer radiation belt due to effective magnetopause shadowing (Hietala et al, ; Kilpua, Hietala, et al, ; Kilpua et al, ; Turner et al, ). Our study also suggests that sheaths of slow ejecta can also compress/erode the subsolar magnetopause significantly, but very rarely beyond the geostationary orbit and also compression/erosion beyond <8 R E occurs typically less than 50% of the sheath duration.…”
Section: Summary and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The effectiveness of sheaths to deplete the belts is partly related to their strong dynamic pressure that can effectively enhance magnetopause shadowing. On the other hand, the average ULF Pc5 and EMIC wave powers in the inner magnetosphere are higher during sheaths than during ejecta (Kalliokoski et al, 2019;Kilpua et al, 2019b).…”
mentioning
confidence: 90%
“…As a consequence, it is expected that the inner magnetosphere responds differently to sheath and ejecta. Recent studies (e.g., Kilpua et al, 2015;Lugaz et al, 2015;Turner et al, 2019;Kilpua et al, 2019b) have indeed highlighted that sheaths and ejecta distinct responses in energetic electron fluxes in the radiation belts. A key characteristic of sheaths is that they cause long and sustained depletions of electron fluxes at wide range of energies and L-shells.…”
mentioning
confidence: 99%